I'll Show You Mine, If You Show Me Yours (ScientificWorldJournal, 2001)
The human genome dominated science news last week. Both Science and Nature lead this week with articles about the simultaneous publication of the human genome sequence by the private company Celera Genomics and the publicly funded Human Genome Project (HGP).